Research on Application of BIM+GIS Technology in Building Life Cycle. Issue 2 (April 2021) - Wu, Bei; Zhou, Rui; Long, Yu; Cai, Xinyue; Li, Bingnan
Abstract: Based on a project, the application of BIM+GIS technology in the whole life cycle of the project building is studied. Selecting the image data based on the fusion of UAV tilt photography and panoramic data, a controllable data management platform is established. In the planning and design stage, the use of technology can reduce the frequency of exploration, check the project for design errors, reduce the number of rework of the project, improve work efficiency. In the construction phase, funding for large-scale projects through image data, using BIM Technology to simulate construction progress, collision check, etc. Reduce the waste of resources; in the operation and maintenance phase, through the management of the information data of the BIM model, so as to provide data support for the maintenance and other work in the later stage of the project.